2018
DOI: 10.18203/2394-6040.ijcmph20181739
|View full text |Cite
|
Sign up to set email alerts
|

Violence against health workforce in Bangladesh: a call for action

Abstract: Violence against health workforce has become a public health concern affecting the lives of the health professionals and the overall health service delivery to a greater extent. Common forms of workplace violence faced by healthcare professionals include verbal abuse, physical assault, bullying, sexual harassment and racial harassment. The scenario is more severe in low and middle-income countries where physicians, nurses and other health workers get exposure to such horrifying experiences in their day-to-day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…31 As a consequence of these violent outbursts, many health care professionals were brutally injured, and few even lost their lives. 32 India has a high burden of WPV similar to other LMICs. The Indian Medical Association (IMA) has reported that 75% of doctors face either physical or verbal abuse at some point of their career.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…31 As a consequence of these violent outbursts, many health care professionals were brutally injured, and few even lost their lives. 32 India has a high burden of WPV similar to other LMICs. The Indian Medical Association (IMA) has reported that 75% of doctors face either physical or verbal abuse at some point of their career.…”
Section: Introductionmentioning
confidence: 96%
“…31 As a consequence of these violent outbursts, many health care professionals were brutally injured, and few even lost their lives. 32…”
Section: Introductionmentioning
confidence: 99%
“…The family member accused the doctor of malpractice when the patient died under the doctor’s care ( Prothomalo, 2020 ). Although a few researchers have started to address the issue of WPV in non-western contexts, no studies have yet been conducted to investigate the nature, causes, or impacts of WPV within Bangladesh ( Khan et al, 2010 ; Hossain et al, 2018 ). The current study aimed to compile incidents of WPV shared by Bangladeshi doctors in an existing large social media forum for doctors, called “Platform.” Findings from this study can help generate information on catalysts of WPV and guide policies and interventions to prevent such events.…”
Section: Introductionmentioning
confidence: 99%